Public Information and Communication Technology Innovation Model within the Government of West Bandung Regency - Rizqi Ghassani; Thomas Bustomi; Lia Muliawaty (Global Writing Academica Researching & Publishing, 2026)
This study aims to analyze the implementation of Public Information and Communication Technology (ICT) innovation and to formulate a Public ICT Innovation Model within the Government of West Bandung Regency. The study is motivated by the suboptimal implementation of various ICT-based innovation programs due to several critical regional innovation factors, including leadership, innovation culture development, the capacity of educated and trained personnel, innovation team development, and measurable work orientation. This research employs a qualitative approach with a descriptive-analytical method through observation, interviews, and document analysis conducted at the Department of Communication, Informatics, and Statistics (DISKOMINFOTIK) and related Regional Apparatus Organizations (OPDs). The findings indicate that although Public ICT innovations have generally been implemented effectively, major obstacles persist, particularly low work and learning culture and rigid bureaucratic structures. On the other hand, innovation optimization is driven by technology push factors, encompassing research and development, production, marketing, and market needs. The study also identifies external interference factors, such as academic involvement, benchmarking with other local governments, and public feedback which significantly contribute to improving and integrating innovation initiatives. Improvement efforts are reflected in the integration of 103 innovations into two main platforms and institutional efficiency through the strengthening of internal human resources. This research proposes a Public ICT Innovation Model as a systematic framework emphasizing integration, innovation curation, centralized coordination through DISKOMINFOTIK, and adaptability to external dynamics. The model is expected to serve as a strategic reference for developing more effective, efficient, and sustainable public ICT innovations at the local government level.